Analisis Faktor Eksternal Dan Internal Dalam Pengembangan Strategi Bisnis Di Maze Cafe Eatery & Pattiserie - Rd. Ghina Fithriyah; Wahidah Nazmi Lailia; Muhammad Raka Alifian Firdaus; Bilal Afriansyah; Fiqri Alief Fahrijal; Siti Mardiana (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study was conducted to examine how external and internal factors influence the development of business strategies at Maze Café, as well as to formulate relevant and applicable strategies in responding to the dynamics of the F&B industry. The research employed a descriptive qualitative approach through direct observation, structured interviews, and documentation from Maze Café’s official social media accounts. The data were analyzed using a thematic analysis method focusing on internal and external factors. The findings indicate that Maze Café has strengths in terms of location, aesthetic concept, and service quality, but shows weaknesses in healthy menu innovation and digitalization. Intense competition and shifting consumer trends pose threats that must be addressed through adaptive strategies. It is concluded that Maze Café needs to implement an aggressive growth strategy through differentiation, digitalization, and product and market development. This research is expected to provide practical contributions to similar culinary MSMEs in facing the dynamic competition of the industry.